10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
BackgroundHIV drug resistance testing plays an important role in optimizing antiretroviral therapy, yet routine testing remains limited in China. This study applied a discrete choice experiment to evaluate patient preferences and willingness-to-pay for HIV drug resistance testing; to inform patient-centered implementation strategies for HIV drug resistance testing.MethodsBetween April and June 2025, people living with HIV were recruited from community healthcare centers in China. Mixed logit models and latent class analysis were used to quantify attribute trade-offs, identify preference heterogeneity, and estimate willingness-to-pay across clinical and demographic subgroups.ResultsAmong 204 participants, out-of-pocket cost was the dominant barrier to uptake, accounting for 62.3% of overall decision importance. Testing after treatment failure (β = 0.862), and doctor recommendation (β = 0.519) were primary determinants of choice (all p < 0.001). Combined testing (p = 0.037), shorter waiting time (3 days: p = 0.008), and high accuracy (p = 0.031) also significantly increased testing preference. Latent class analysis identified two distinct subgroups. Class 1 (failure-driven) prioritized testing after treatment failure (β = 3.547) but showed a negative preference for combined testing and high accuracy (all p < 0.05). Class 2 (service-oriented) strongly valued doctor recommendation and high accuracy (all p < 0.01). Older participants (≥50 years old) had a higher willingness-to-pay for doctor recommendation than the younger (240.2 vs 115.7 CNY), while younger showed higher WTP for combined testing and high accuracy.ConclusionsReducing financial barriers, strengthening provider recommendations, and tailoring testing services to different patient preference patterns may improve HIV drug resistance testing uptake. These findings support patient-centered implementation strategies to promote earlier and more routine HIV drug resistance testing in China.